Molecular Docking and Pharmacophore Analysis of Compounds from Ginger (Zingiber officinale) as Inhibitor for Dengue DEN2 NS2B/NS3 Serine Protease - Neni Frimayanti; Enda Mora; Rindiyani Rindiyani (ALCHEMY Jurnal Penelitian Kimia, 2023)
Dengue hemorrhagic fever (DHF) is a disease caused by the dengue virus (DENV). Dengue virus can enter the human body through the Aedes aegypti and Aedes albopictus mosquitoes. According to the Indonesian Ministry of Health, dengue hemorrhagic fever (DHF) is still a serious health problem in Indonesia. The type of dengue virus serotype most commonly found to cause infection in the human body is the DENV-2 serotype. This study aims to determine whether Ginger (Zingiber officinale) isolate compounds have potential as dengue DEN-2 NS2B/NS3 inhibitors. Samples used are compounds with IUPAC names (S)-5-hydroxy-1-(4-hydroxy-3-methoxyphenyl) octan-3-one (4-gingerol) and (S)-5-hydroxy-1-(3-methoxy-4-methylphenyl) decan-3-one. The method used is molecular docking and Pharmacophore using the MOE (Molecular Operating Environment) 2022.0901 software package. The results obtained based on the observed parameters of the two compounds isolated from ginger (Zingiber officinale) could be estimated as potential dengue DEN2 NS2B/NS3 inhibitors.